Circus art as an object of cultural studies (Journal of Philosophy Culture and Political Science, 2019)
This article analyzes the formation and development of circus art and mass laughter as a cultural phenomenon, which requires the study of the specifics of the cultural consciousness of people, the removal of the primary source and culture, as well as the consideration of this type artistic creativity as a unique cultural object.The roots of circus art that have arisen in everyday life, related to the need for a popular culture of laughter and the need to «turn people’s lives into a holiday.»The cultural formation and development of the circus begins with the folk tradition, the art of laughter. Laughter is an integral part of the circus. Laughter is cheerful, sociable, hedonistic and informative. It is also a universal phenomenon accompanied by the development of world civilization. Circus art is always focused on the excitement, the astonishment of the audience. In this art the flame of youth, wisdom of the ages, beauty and courage, enthusiasm, artistic decision and mixing fantasy. Circus show is designed to give viewers the opportunity to get into the fairy world, to give a unique holiday and unforgettable mood.As a result of studying the history of art, it was proved that the circus took place in ancient times, from the beginning of civilization to all forms of folklore.Key words: art, circus, laughter, mass culture, tradition, cultural phenomenon, folk culture.